A study on quality of work life among lecturers in UiTM Kelantan / Anis Salihah Che Berhanuddin , Che Muhamad Luqman Che Lah and Siti Nur Atiqah Mohd Shafie - Che Berhanuddin, Anis Salihah; Che Lah, Che Muhamad Luqman; Mohd Shafie, Siti Nur Atiqah (2019)
Quality of work life is an employee’s self-reported satisfaction with a job. This study aim is to identify the significance factors (stress at work, work occupy, job and career satisfaction and working condition) towards the quality of work life (QWL) among the lecturers in UiTM Kelantan. Besides, this study also carried out to study the significant mean difference between quality of work life (QWL) of lecturers in UiTM Kelantan and some of demographics variables (age, gender, educational qualification, work experience and income level). The sample of this study consists of 204 lecturers in UiTM Kelantan. This sample is selected by using simple random sampling and the data collection method that applied in this study is self-administered questionnaire. For the analysis of this study, the researcher used structural Equation Modelling (SEM), Analysis of Variance (ANOVA) and Independent T-Test. The results show working condition and job and career satisfaction influence the quality of work life (QWL) while the work occupy and stress at work are negatively correlate to the quality of work life (QWL). The results for demographic variables show there is no mean difference between the groups in each variable